2015
DOI: 10.2147/opth.s71246
|View full text |Cite
|
Sign up to set email alerts
|

Malignant hypertensive retinopathy as a presenting sign of an occult dead fetus

Abstract: We report one case of malignant hypertensive retinopathy as a presenting sign of fetal death in utero. Ophthalmic examination (including intravenous fluorescein angiography and optical coherence tomography) and obstetric and systemic evaluation were performed, providing a multidisciplinary approach. A 33-year-old overweight woman (body mass index 47 kg/m2) with no systemic or ocular known disease was admitted to our emergency department with a one-week history of bilateral vision loss and no systemic complaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Araújo J et al reported a case of a woman with malignant hypertensive retinopathy who was discovered to bear a dead fetus. 15 Our study found that obstetric complications were common in women having retinal changes compared to those without the changes. Some of these complications might be life threatening, viz: HELLP syndrome and oliguria.…”
Section: Discussionmentioning
confidence: 57%
“…Araújo J et al reported a case of a woman with malignant hypertensive retinopathy who was discovered to bear a dead fetus. 15 Our study found that obstetric complications were common in women having retinal changes compared to those without the changes. Some of these complications might be life threatening, viz: HELLP syndrome and oliguria.…”
Section: Discussionmentioning
confidence: 57%
“…In a review of the literature, we identified 43 case reports and case series documenting serous retinal detachment during pregnancy. Our review included 97 women diagnosed with preeclampsia with a median gestational age at presentation of 31.9 weeks (range 20–40 weeks) [ 5 , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. Of cases with blood pressure data reported (90 of 97), only one patient was normotensive.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 15 ] It not only affects general population with hypertension, but also occurs in pregnancy (also known as hypertensive retinopathy of pregnancy, HTRP), which results in high risk for both mother and fetus. [ 16 – 18 ] In addition, many patients with HTRP often experience psychological disorder (PD), such as depression and anxiety. [ 19 , 20 ] Thus, it is very important to manage this disorder as early as possible.…”
Section: Introductionmentioning
confidence: 99%